Critical Analysis of AI-Produced Media: A Study of the Implications of Deepfake Technology - Septiawan, Riski (Green Publisher Indonesia, 2024)
This study examines the implications of AI-generated media, particularly regarding deepfakes, on how we consume and perceive information. With the increasing presence of AI-generated media, it is crucial to question how they influence media literacy and the potential for misinformation. The research finds that AI-generated media has the potential to manipulate and deceive audiences, blurring the lines between reality and fiction. Its impacts are highly significant to examine its effects on our ability to critically evaluate information and make informed decisions.